Experiencias de personas con diversidad funcional auditiva y optómetras en la atención en salud visual (2021)
Objective: Describe the experience of people with hearing functional diversity and visual health professionals regarding the dynamics that occur within health care. Methodology: Qualitative interpretive study. Semi-structured interviews were carried out by telephone, given the condition of pandemic by covid-19, to people with hearing functional diversity, optometrists and sign interpreters. For the analysis process, the methodological design from Taylor and Bogdan was used. Results: From the analysis carried out, two categories emerge: Lack of knowledge of health professionals about the meanings of functional auditory diversity and positive practices for clinical care. The lack of knowledge of the professionals can be explained by the lack of training for the care of diversity, which is reflected in the lack of minimum tools to implement to facilitate communication in the context of clinical care. Some positive experiences are identified in relation to the implementation of some practices in which communication mechanisms are carried out in which the right to health of those who attend the consultation is guaranteed. Conclusions: The findings show the barriers to the establishment of communication in the exercise of optometric care; There are still gaps to guarantee accessibility for people with hearing functional diversity.